Coral snake envenomation induced acute pancreatitis - Erum Sajjad; Sumayya Sami; Iffat Khanum (The Egyptian Journal of Internal Medicine)
Abstract Background Coral snakes belong to the elapid group. They are venomous and are highly neurotoxic, but their bites are not considered lethal to life. We describe a case of coral snake poisoning leading to acute pancreatitis, which is a very rare complication reported in literature after snake envenoming. Case presentation A young female patient presented with complaints of generalized weakness, muscle spasms, and respiratory distress after the coral snake bite 1 day ago. She had bilateral ptosis and muscle power of 3/5 in all her limbs at the time of presentation for which she received anti-venom along with low-dose intravenous neostigmine in our hospital which improved her ptosis and muscle weakness gradually over 3 days. On day 4th of her admission, she developed severe generalized abdominal pain and tenderness in the epigastrium. Acute pancreatitis was diagnosed after appropriate investigations which was treated with supportive therapy, and the patient improved clinically. Conclusion Acute pancreatitis after coral snake envenomation is a rare and serious complication. Timely identification and initiation of appropriate management can improve clinical outcome of the patient.